Analisis Faktor-Faktor Yang Mempengaruhi Capaian Realisasi Anggaran Pada Satuan Kerja Rumah Penyimpanan Benda Sitaan Negara Di Wilayah Jakarta Barat - Lawe Anasta; Dedi Purwadi (Profita : Komunikasi Ilmiah Akuntansi dan Perpajakan, 2020)
The low absorption of the budget as a manifestation of the estimated performance to be achieved during a certain period of time and expressed in financial terms has an impact on the slow realization of the implementation of government programs and activities. This is especially true if this occurs in the work unit for the state's confiscated objects storage house which is the place for storing state confiscated objects for the purposes of judicial proceedings. This study aims to examine the effect of procurement of goods and services, budget planning, human resources, performance-based budgeting systems on budget realization in the work unit for storing confiscated objects of the state of West Jakarta. The sampling technique used the purposive sampling method of 100 respondents. The data collection method is a survey using a questionnaire distributed to respondents. Data were analyzed using multiple regression analysis. The results of this study conclude that: procurement of goods and services, human resources, and performance-based budgeting systems have a significant positive effect on budget realization, while budget planning has a negative and insignificant effect on budget realization.